Selection on Spinosad and Emamectin benzoate insecticide resistance level in field-collected Diamondback Moth - Hasran, Nabihah (2016)
Plutella xylostella (L) also known as Diamondback Moth (DBM) is the main insect of crucifers such as cabbage, broccoli, canola and cauliflower. It is also the most destructive pest of cruciferous worldwide including Malaysia. DBM has become difficult insect to control in the world because of its resistance evolution to every insecticides class used extensively against it and due to repeated use of same insecticide in controlling it. DBM developed resistant to many insecticides due to the polyvoltin features and overlap of generations. Many of the resistant study conducted concentrate on the resistant level of insecticide in DBM. However, there is a need to understand how fast a resistance toward specific insecticide developed in DBM. The objective of this study was to determine the increase of insecticide resistant levels in DBM through selection process. In this study, two types of insecticides (Spinosad and Emamectin) were tested on DBM. DBM from organic farm were collected and cultured in glasshouse. The population were cultured until four generations. Bioassay on parent population shown Spinosad has higher toxicity level with LC50 at 15.106 ppm. Compared to Emamectin with LC50 at 48.660 ppm. Insecticide selection experiments were conducted with feeding the DBM population with LC15 values from parent and F2 bioassay experiment. The insecticide selection shown DBM developed resistant to Emamectin was faster compared to Spinosad. The DBM resistance ratio to Emamectin was 1.76 and 1.84 fold for F2 and F4, respectively. While, the resistance ratio to Spinosad was 1.58 and 1.28 fold for F2 and F4, respectively.